Key Issues in Central America Health Reforms : Diagnosis and Strategic Implications, Volume 1. Synthesis of Findings - World Bank (Washington, DC, 2012)
The main objective of this report is to identify and analyze the most pressing health sector issues in the sub region of El Salvador, Guatemala, Honduras, and Nicaragua (referred to as CA4) while building on the successes already attained, in order to lay the groundwork for discussing and refining strategies and policies in CA4. It will focus on analyzing (a) CA4 health sector performance, measured by financial protection and a subset of health indicators; and (b) health system functions of financing and service delivery. The report also addresses three topics that CA4 stakeholders selected as their main areas of interest: (a) decentralization processes initiated in these countries; (b) the design and implementation of alternative strategies to improve access to basic maternal and child health care services: and (c) the high prevalence of malnutrition. The synthesis of findings can be found in volume 1 of the report. In volume 2, aside from the introduction, the report comprises five chapters: Chapter 2 discusses the different aspects that characterize the health sector of these countries: health care financing, financial coverage and protection, efficiency and equity in the allocation of resources and service coverage and utilization. Chapter 3 describes the extent and consequences of the various decentralization processes. Chapter 4 presents the different strategies being followed to improve access and extend basic health services, and Chapter 5 focuses on malnutrition and strategic considerations for cost effective programs in CA4.